1999
DOI: 10.1016/s0014-5793(99)00245-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of heparin with annexin V

Abstract: The energetics and kinetics of the interaction of heparin with the Ca +P and phospholipid binding protein annexin V, was examined and the minimum oligosaccharide sequence within heparin that binds annexin V was identified. Affinity chromatography studies confirmed the Ca +P dependence of this binding interaction. Analysis of the data obtained from surface plasmon resonance afforded a K d of V21 nM for the interaction of annexin V with end-chain immobilized heparin and a K d of V49 nM for the interaction with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 26 publications
2
38
0
5
Order By: Relevance
“…It has also been shown that Ca 2þ is an essential activator of a heparin degrading enzyme, heparinase I, in which the heparin-Ca 2þ complex is the true enzyme substrate, whereas Ca 2þ -free heparin is a competitive inhibitor [147]. Annexin V, an abundant anticoagulant and phospholipid binding protein binds HS in a calcium ion-dependent manner, binding via two binding sites on opposite faces of the protein [148,149]. The phospholipid binding and calcium-dependent annexin I has been reported as requiring N-and 2-O-sulfate groups for binding [150].…”
Section: Cation Binding To Heparan Sulfate/heparin and Its Effectsmentioning
confidence: 99%
“…It has also been shown that Ca 2þ is an essential activator of a heparin degrading enzyme, heparinase I, in which the heparin-Ca 2þ complex is the true enzyme substrate, whereas Ca 2þ -free heparin is a competitive inhibitor [147]. Annexin V, an abundant anticoagulant and phospholipid binding protein binds HS in a calcium ion-dependent manner, binding via two binding sites on opposite faces of the protein [148,149]. The phospholipid binding and calcium-dependent annexin I has been reported as requiring N-and 2-O-sulfate groups for binding [150].…”
Section: Cation Binding To Heparan Sulfate/heparin and Its Effectsmentioning
confidence: 99%
“…Among separation and interaction techniques, CE has been proved to be very attractive due to the advantages of high separation efficiency, great flexibility, simple operation, short analysis time, and low consumption of samples and buffers [9]. In addition, the interaction between molecules can be directly observed under physiological conditions, without prior immobilization steps, as is required in affinity chromatography and surface plasmon resonance spectrometry [28][29][30][31][32][33][34][35][36] that pose a problem of steric hindrance [37][38][39]. It would also be possible, by using CE, to study interactions of individual components in a mixture and to determine binding parameters simultaneously [40].…”
Section: Introductionmentioning
confidence: 99%
“…Anx V binds with high affinity to such negatively charged phospholipids as phosphatidylserine. They also bind to another polyanion group, glycosaminoglycans, such as heparin [18][19][20]. Therefore, it is reasonable to assume that Anx V was thus adsorbed by DS bound cellulose beads because DS also contain repeating negatively charged units.…”
Section: Discussionmentioning
confidence: 99%